Pengaruh Citra Merek, Harga dan Kualitas Produk terhadap Minat Beli Pada Roti Khasanah Sari Cabang Dukuh Zamrud - Isti Pujihastuti (Fakultas Ekonomi Universitas Islam 45, 2024)
This study aims to examine the effects of brand image, price, and product quality on consumer purchase intention for Khasanah Sari Bread at the Dukuh Zamrud Branch. The research employed a descriptive quantitative method, using purposive sampling with 100 respondents who were potential consumers willing to purchase the product. Data were analyzed using multiple linear regression. The results show that brand image has a significant effect on purchase intention, indicating that a positive brand perception increases consumers’ willingness to buy. Price also has a significant effect, suggesting that an appropriate price consistent with perceived value supports purchasing decisions. However, product quality does not significantly influence purchase intention, implying that it is not the primary factor driving consumer decisions. Collectively, brand image, price, and product quality have a joint effect on purchase intention. In addition, external factors such as promotion, customer service, and customer satisfaction may also shape purchasing behavior. Therefore, businesses should prioritize strengthening brand image and pricing strategies to increase consumer interest.